Increased Protein Consumption and Nitrogen Retention of Sheep Fed Sodium Bicarbonate and Fermented Concentrate - Pajriyah, Wafiq Siti Nur; Suryapratama, Wardhana; Suhartati, F. M.; Rahayu, Sri; Rimbawanto, Efka Aris (Faculty of Agriculture, 2025)
This study aimed to evaluate the effects of sodium bicarbonate and fermented concentrate feed on protein consumption and nitrogen retention in sheep. The experiment utilized 18 male local sheep, aged 78 months, with an average body weight of 19.442.37 kg. The animals were fed a diet consisting of ammoniated rice straw (25%) and concentrate (75%). The study employed an in vivo experimental approach using a Randomized Complete Block Design (RCBD), with initial body weight as the blocking factor and six replicates per treatment group. The treatments were as follows: P1= ammoniated rice straw (25%) + concentrate (75%); P2= ammoniated rice straw (25%) + concentrate (75%) + sodium bicarbonate; and P3= ammoniated rice straw (25%) + concentrate (75%) fermented with Saccharomyces cerevisiae (3%) + sodium bicarbonate. The measured variables were protein consumption and nitrogen retention. Data were analyzed using analysis of variance (ANOVA), followed by the Honestly Significant Difference (HSD) test. The mean protein consumption was 129.5810.84 g/head/day (P1), 127.3815.46 g/head/day (P2), and 161.115.32 g/head/day (P3). The mean nitrogen retention was 84.515.50 g/head/day (P1), 83.657.59 g/head/day (P2), and 117.1612.46 g/head/day (P3). HSD analysis revealed that the combination of sodium bicarbonate and fermented concentrate feed (Saccharomyces cerevisiae) resulted in the highest protein consumption and nitrogen retention, with increases of 24.33% and 38.64%, respectively, compared to other treatments.